Protective factors as predictors of resilience traits in male and female high school students - TERRY, TAN (Archīum Ateneo, 2010)
Because no one is able to avoid adversity completely, this study focuses on the resilience traits of the individual and their protective factors. Adapting WestEd's concept on resilience, the California Healthy Kids Survey was used to measure the protective factors and resilience traits of the male and female students. The survey was administered to sophomore students which include 74 male and 89 female students. The t-test for Independent Samples and Multiple regressions were computed, to compare the protective factors and resilience traits of the male and female students, and to determine the protective factors that predict resilience traits. Results reveal that there are no significant difference between the protective factors and resilience traits of the male and female students. However, caring relationships in school and among peers are strong predictors of resilience traits for the male students, while opportunities for meaningful participation in school is a strong predictor of resilience traits for the female students.